Numerical Study of Convection Air Currents Around a Hot Cylinder Inside a Triangular Cavity - Akeel Abdullah Mohammed; Ansam Adil Mohammed; SHYLESHA CHANNAPATTANA (مجلة النهرين للعلوم الهندسية, 2023)
A numerical study was performed of natural laminar convective heat transfer to its concentrated triangular enclosure around a horizontal circular cylinder. The air-filled enclosure kept the inner and outer cylinders at uniform temperatures. The Boussinesq density approximation to the momentum problem and the control volume approach iteratively resolved the governing equations to explain buoyancy. CFD results show that the velocity behavior increases by increasing Ra, so the stream lines becomes more sluggish and less uniform behavior and vortices gets less circulated pattern. The rotation angle ? has significant effect on vortices, at 90o gives the higher range of velocity zones of free convection with higher range. The thermal boundary layer seems to be larger in rr=0.455 as compared with rr=0.345 and decreases by increasing ?. The larger variation of isotherms and thermal boundary layer appears at lower ? because the higher heat transfer rate occurs at higher ? and becomes maximum at 90o. Eight correlations of average Nusselt number have been deduced as a function of Rayleigh number for the taken values of aspect ratio and enclosure angles of rotation and inclination.